The Relationship between Human Being and Animal: The Study of the Concepts of Khalifah and the Animals in the Quran - Safitri, Lis; Nuskhi, Muhammad; Muatip, Krismiwati; Purwaningsih, Hermin; Setiana, Lucie (ANIMAL PRODUCTION, 2018)
Islam does not only talk about the procedure of worshiping (ibadah), but also related to daily activities (muammalah), including how to treat animals. Understanding the relationship between human being and animals is the basis for further studies of animals in Islam. This study is library research using the descriptive-inferential method with the purpose to elaborate on the position of the animal against the human being based on the concept of the human being as khalifah. The Quranic verses about khalifah and animals in the Quran have been collected using thematic interpretation method of al-Farmawi. The data have been analyzed using philosophical and theological approaches to find the concept of khalifah and the position and the purpose of animal life in the Quran. The result showed that God gives rightful supremacy on earth to human beings for upholding God’s law and guiding the creatures to their purpose of creation, because of their blessed potentials i.e. emotion, intelligence, and natural disposition for grasping the truth and goodness (fitra). Human being has to treat animals in line with the objective of their creation, i.e. God’s creature, the Signs of God’s Power, viands for human being and the other creatures, ride, and the lesson of life.